Emerging Technologies for Authorization and Authentication First International Workshop, ETAA 2018, Barcelona, Spain, September 7, 2018, Proceedings - Saracino, Andrea; Mori, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the proceedings of the First International Workshop on Emerging Technologies for Authorization and Authentication, ETAA 2018, held in Barcelona, Spain, in September 2018. The 10 papers presented in this volume were carefully reviewed and selected from 16 submissions. They were organized in two parts: authentication and authorization techniques and violation detection and countermeasures. .
Authentication and authorization techniques -- Authentication and authorization for interoperable IoT architecture -- Bringing Access Control Tree to Big Data -- SNAPAUTH: A Gesture-based Unobtrusive Smartwatch User Authentication Scheme -- A Protocol to Strengthen Password-Based Authentication(short paper) -- Managing Private Credentials by Privacy-Preserving Biometrics -- Policy Support for Autonomous Swarms of Drones -- Violation Detection and Countermeasures -- A Logic-Based Reasoner for Discovering Authentication Vulnerabilities between Interconnected Accounts -- Towards a Framework for Testing the Security of IoT Devices Consistently -- Misuse Detection in a Simulated IaaS Environment -- Dissuading Stolen Password Reuse.
Keywords: Data protection; Software engineering; Application software; Computers; Computer communication systems; Biometrics (Biology).; Security; Software Engineering/Programming and Operating Systems; Information Systems Applications (incl. Internet).; Computing Milieux; Computer Communication Networks; Biometrics